CAUSES OF SOCIO-ECONOMIC STRATIFICATION OF REGIONS AND INTERNATIONAL APPROACHES TO ADDRESSING IT (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyzes the causes of socio-economic stratification among regions and examines international experiences in addressing these disparities. Differences between regions arise due to factors such as the distribution of geographic and natural resources, education and skill levels, political systems and governance, infrastructure, and global economic changes. The study reviews practical strategies and solutions based on the experiences of the European Union, China, and Canada in mitigating regional disparities. The article proposes policies that nations and global organizations should implement to prevent socio-economic inequality and ensure sustainable development. It emphasizes the importance of reducing interregional differences through education, innovation, industrial diversification, and regional investment attraction.